2005
DOI: 10.1073/pnas.0507440102
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in estrogenic regulation of neuronal activity in neonatal cultures of ventromedial nucleus of the hypothalamus

Abstract: Estrogenic effects have been implicated in sexual differentiation of brain and behavior, in part by affecting neuronal activity in the ventromedial nucleus of the hypothalamus (VMN). We report here a remarkable sex difference in estrogenic regulation of neuronal activity in male vs. female neural networks. Spontaneous synaptic currents originating from a population of neurons were recorded in primary VMN cultures using the whole-cell patch-clamp technique. Treatment with 17␤-estradiol (E2, 10 nM) for 24 h indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Similar to the previous reports, a large proportion of the neurons cultured in the estrogen-free medium had epileptiform bursting activities in the present study, and the low dose 17-β-estradiol (~0.1 ng/ml) had a suppressive effect, whereas the high dose 17-β-estradiol (1 ng/ml) had a promoting effect on the neuronal excitability change, forming a U-shape-like dose-dependent action on the neuronal excitation change. This effect may explain the differential action of the estrogen receptor stimulation caused increase or decrease of neuronal excitability in various studies (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similar to the previous reports, a large proportion of the neurons cultured in the estrogen-free medium had epileptiform bursting activities in the present study, and the low dose 17-β-estradiol (~0.1 ng/ml) had a suppressive effect, whereas the high dose 17-β-estradiol (1 ng/ml) had a promoting effect on the neuronal excitability change, forming a U-shape-like dose-dependent action on the neuronal excitation change. This effect may explain the differential action of the estrogen receptor stimulation caused increase or decrease of neuronal excitability in various studies (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 90%
“…17-β-estradiol has been reported to increase the excitability of gonadotrophin-releasing hormone neurons (26), medial vestibular nucleus neurons in brain stem (27) and hippocampal neurons (28). By contrast, estrogen receptor activation has also been reported to decrease neuronal excitability by indirectly changing the local neurotransmitter release (29), particularly by changing the interaction with GABAergic neurons (30,31). Our previous study also indicated that on the same hippocampal neuron, a weak estrogen receptor agonist, phenol red, could have a U-shape-like activation-inhibition-activation effect on the epileptiform bursting activities: Low and high concentrations of phenol red all induced the epileptiform bursting activities in the cultured hippocampal neurons, while the middle concentration (~28 µM) of phenol red suppressed this activity (13).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary tests with a combination of a pre-spike LTP window and a post-spike LTD window (STDP) suggest these may be essential for look-ahead plasticity with realistic (shorter) integration times. It is important to note that Zhou et al (2005) have shown both LTP and LTD in slice preparations of entorhinal layer II/III pyramidal neurons.…”
Section: Discussionmentioning
confidence: 98%
“…17-β-estradiol increases the excitability of gonadotrophin-releasing hormone neurons [8], medial vestibular nucleus neurons in brain stem [9] and hippocampal neurons [10] through either membrane or intracellular mechanisms. Estrogen has also been reported to decrease neuronal excitability by indirectly changing the local neurotransmitter release [11] particularly by changing the interaction with GABAergic neurons [12], [13]. In addition to the modulation of the neuronal excitability, activation of estrogen receptors could stimulate the spinogenesis [14], [15], [16] or affect the brain development by activating its two receptor subtypes: ERα and ERβ [17].…”
Section: Introductionmentioning
confidence: 99%